2009
DOI: 10.1002/mnfr.200800457
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of colon carcinogenesis by apple juice in vivo: Impact of juice constituents and obesity

Abstract: It is estimated that 75-85% of all chronic diseases are linked to lifestyle-related and environmental factors. The development of colon cancer is positively associated with obesity and inversely associated with the intake of dietary fibre, fruit and vegetable. Apple juice is the most widely consumed fruit beverage in Germany. It contains a specific spectrum of polyphenols and other components that may reduce the risk of colon cancer. Epidemiologic studies suggest an inverse correlation between apple consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 97 publications
0
17
0
Order By: Relevance
“…For example, epidemiological studies suggest an inverse correlation between apple consumption and colon cancer risk. However, under the cancer promoting condition of obesity, apple juice did not show cancer-preventive bioactivity (Koch et al , 2009). Some intervention trials with pure carotenoids did not show any effect on cancer risk, and in fact other trials have shown increased risk (Stahl and Sies, 2005).…”
Section: Cancermentioning
confidence: 98%
“…For example, epidemiological studies suggest an inverse correlation between apple consumption and colon cancer risk. However, under the cancer promoting condition of obesity, apple juice did not show cancer-preventive bioactivity (Koch et al , 2009). Some intervention trials with pure carotenoids did not show any effect on cancer risk, and in fact other trials have shown increased risk (Stahl and Sies, 2005).…”
Section: Cancermentioning
confidence: 98%
“…Among food categories rich in antioxidant components, apple fruits seem particularly interesting, both for the number of varieties and their high content of antioxidants456, and for their known chemo-preventive effects against colorectal cancer78910. Recently, the content of phenolic compounds in different apple varieties has been compared11.…”
mentioning
confidence: 99%
“…Moreover, apples are rich in phenolic compounds [10], that are widely discussed as promising candidates for prevention of cancer and inflammation [2,11]. Apple and AJ are reported to increase antioxidant levels in humans [12] and have been tested as cancer chemopreventive both in vitro [13] and in humans [14,15]. Beside cancer chemoprevention, apple polyphenols have been reported to have other in vitro and in vivo physiological properties, such as antiallergenic and anti-caries activity, and inhibitory activity against some enzymes and receptors involved in pathological processes [2,16].…”
Section: Introductionmentioning
confidence: 99%